'Everyone is trying to outcompete each other': a qualitative study of medical student attitudes to a novel peer‐assessed undergraduate teamwork module. Issue 5 (23rd March 2022) - Watson, Helen R.; Dolley, Mary‐Kate; Perwaiz, Mohammad; Saxelby, Jocelyn; Bertone, Gianluca; Burr, Steven; Collett, Tracey; Jeffery, Robert; Zahra, Daniel
Abstract : The centrality of teamwork in ensuring the effective functioning of institutions across all sectors is undeniable. However, embedding teamwork into higher education has been hampered due to a range of deeply entrenched practices associated broadly with the foregrounding of knowledge, beliefs about the place of skill training and routines of assessment. As a result, despite an urgent need to address teamwork, little progress has been made with respect to progressing teamwork education. We have designed and evaluated a novel teamwork module delivered to fourth‐year undergraduate medical students involving placements, a cocreated piece of work, reflection and summative peer assessment. This paper aimed to investigate whether the module increased students' insight into teamwork, including their own skill development, and whether their perceptions of teamwork changed. Throughout the evaluation, students played a key role, with four final‐year medical students working alongside others in the multidisciplinary project team. Five distinct themes emerged from our in‐depth, semi‐structured interviews: (a) importance and meaning; (b) insight into skill development; (c) transferability; (d) peer assessment; and (e) resistance to teamwork education. Themes had positive and negative components, and student perceptions changed in multiple ways after experiencing a longitudinal educational opportunity to develop their teamwork skills. Before practice, students focused on superficial explanations and on where they might improve. In contrast, after practice, students conveyed deeper insights, contextualisation, focus on how they might improve, and shared structured reflection. Abstract : This article explores medical students' perspectives on teamwork, in the context of a peer‐assessed teamwork module. We discuss our attempts to develop and assess teamwork in UK undergraduates and consider the challenges of teamwork education and assessment. Here, we present a detailed qualitative analysis of our students' experiences and discuss good practice in teaching this crucial transferable skill.